Membran Berbasis Β-Trikalsium Fosfat Sebagai Membran Barier Pada Guided Bone Regeneration: Tinjauan Naratif - Maria Rini Wulan Dhari; Eddy Eddy; Rosalina Tjandrawinata; Tansza Permata Setiana Putri (Jurnal Sains dan Kesehatan, 2026)
Guided Bone Regeneration (GBR) relies on a barrier membrane to prevent soft tissue invasion in the wound area and maintain space for bone formation. Conventional membranes generally function as a passive barrier without enhancing osteogenesis. Membranes fabricated with the addition of β-TCP were developed to enhance membrane bioactivity. This review aims to evaluate the role of β-TCP as a bioactive component in barrier membranes used in GBR procedures. The study used a narrative review approach with literature sources from PubMed, Google Scholar, and ScienceDirect in the period 2016–2026. The keywords used included “guided bone regeneration," “barrier membrane," and “β-tricalcium phosphate." The selected articles were English-language experimental studies with relevant topics. A total of 7 articles met the inclusion criteria. The incorporation of native β-TCP showed increased osteoconductivity, hydrophilicity, and mechanical strength of the membrane. The release of calcium and phosphate ions plays a role in increasing osteoblast proliferation and osteogenic marker expression. In vitro and in vivo studies also demonstrated increased new bone formation and improved regeneration space maintenance compared to conventional membranes. The optimal concentration of β-TCP varies depending on the polymer matrix. β-TCP-based membranes have the potential to act as bioactive barrier membranes that not only act as a barrier but also support bone regeneration. Further research, particularly human clinical trials, is needed to confirm their effectiveness and safety.